Kebijakan Negara dalam Keterlambatan â€ŽPengurusan Akta Kelahiran Anakâ€Ž - nafi' mubarok (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2016)
Abstract: Certificate of birth as the legal identity of a child and the state legal recognition to the existence of a child, relating to citizenship and their rights as citizens. Unfortunately, the still high number of Indonesian children who do not have a birth certificate that is caused by (1) the problem of cost, (2) families are less aware of the importance of birth certificates, and (3) lack of completeness of the data/documents. In fact, birth registration is part of a civil registry system that provides protection for the human rights of the status of social and individual benefits for children. At the end of this paper concluded that: (1) a birth certificate is a basic right for children, so that every child should memiliknya; (2) The Government of Indonesia is a major carrier of liability for the protection of children's rights, making it responsible for the "do not pass laws or adopt a policy ram rights of the child"; (3) the State had given ease in handling a birth certificate with a "no charge", but the problem is the maintenance of a late birth certificate, where there is an additional court order and an administrative fine; and (4) because of the importance of birth certificates for children, it is necessary to review the policy of "court decision" and "administrative penalties" for late taking care of the birthÂ Abstrak: Akta kelahiran memiliki nilai penting sebagai identitas hukum seorang anak dan pengakuan negara secara hukum terhadap keberadaan seorang anak, berkaitan dengan kewarganegaraan dan hak-haknya sebagai warga negara. Sayangnya, masih tinggi jumlah anak Indonesia yang belum memiliki akta lahir yang disebabkan oleh (1) permasalahan biaya, (2) keluarga kurang menyadari pentingnya akte kelahiran, dan (3) kurang kelengkapan data/dokumen. Padahal, pencatatan kelahiran merupakan bagian dari sistem pencatatan sipil yang memberikan perlindungan bagi HAM atas status sosial dan manfaat individual bagi anak. Di akhir tulisan ini disimpulkan bahwa: (1) akta kelahiran merupakan hak dasar bagi anak, sehingga setiap anak harus memiliknya; (2) Pemerintah Indonesia merupakan pengemban kewajiban utama bagi perlindungan hak anak, sehingga bertanggung jawab untuk â€œtidak mengesahkan undang-undang atau mengeluarkan kebijakan yang melanggarkan hak-hak anakâ€; (3) Negara telah memberikan kemudahan dalam pengurusan Akta Kelahiran dengan â€œtanpa dipungut biayaâ€, namun yang menjadi masalah adalah pengurusan akta kelahiran yang terlambat, dimana ada tambahan penetapan pengadilan dan denda administratif; dan (4) karena pentingnya akta kelahiran bagi anak, maka perlu peninjauan ulang kebijakan â€œpenetapan pengadilanâ€ dan â€œdenda administratifâ€ bagi yang terlambat mengurus akta kelahiran.